Simulating ATM traffic shaping using OPNET - Teo, Kok Eng. (2008)
The goal of using traffic shaping is to maximize the usage or throughput of ATM networks especially in the area of multimedia. Traffic shaping is part of the set of procedures in ATM traffic management whose primary objective is to protect the ATM network and end-systems from congestion in order to promote efficient use of network resources.